VARIABEL – VARIABEL YANG MEMPENGARUHI NILAI PERUSAHAN MAKANAN DAN MINUMAN (Studi Pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia) - Rizky Widi Saputra; Harlen dro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The creation of firm value can provide a positive impact to the owner of the company or shareholders. The purpose of this research is to examine the influence of firm size, profitability, assets growth, sales growth, capital structure and risk financial to the firm value which is proxied to price-book value. The population in this study is a food and beverage company that is listed on the Indonesia Stock Exchange during the period 2009 to 2012. Samples were taken by purposive sampling technique that is based on specific criteria, so obtained a sample of corporate data 12 food and beverage companies. Tested in this study used multiple regression analysis. From the results of multiple regression analysis known that firm size, profitability, assets growth, sales growth, capital structure and risk financial simultaneously affect firm value. Profitability, capital structure and risk financial has positive effect and significant on firm value, with assets growth has negative effect and significant on firm value. Besides firm size and sales growth has negative effect on firm value significantly. Keywords: Firm Value, Firm Size, Profitability, Assets Growth, Sales Growth, Capital Structure, Financial Risk.